2022
DOI: 10.1111/petr.14341
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus‐related cancer risk for solid organ transplant recipients during adult life and early prevention strategies during childhood and adolescence

Abstract: Malignancies are among the top three causes of patient death in pediatric and adult kidney transplant (KT) recipients according to the North American Pediatric Renal Trials and Collaborative Studies 2014 Annual Report and the U.S. Renal Data System 2020 Annual Data Report. Transplant professionals know their patients walk a tightrope, being potential victims of either underimmunosuppres-sion that leads to rejection on one side, or overimmunosuppression that leads to infections and malignancies on the other sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Surprisingly, a recent study of children with CKD showed that growth and sexual maturation are only slightly delayed compared to healthy subjects, which is contrary to what it was previously thought (4, 71), therefore it is important that they are administered the HPV vaccine without delays (60). In general, routine pediatric immunizations in KT candidates and recipients are more likely to be administered by their primary care providers, while vaccines that differ from the routine schedules, including the HPV, are more likely to be administered by transplant professionals, who are likely to be more familiar with dosing them appropriately (4,67). Thus, it is important for both general pediatricians and pediatric transplant nephrologists to be aware of the immunization guidelines for KT candidates and recipients and stay in close communication, to ensure an ongoing fully immunized status for their patients (4).…”
Section: Discussion: Strategies To Improve the Suboptimal Hpv Immuniz...mentioning
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, a recent study of children with CKD showed that growth and sexual maturation are only slightly delayed compared to healthy subjects, which is contrary to what it was previously thought (4, 71), therefore it is important that they are administered the HPV vaccine without delays (60). In general, routine pediatric immunizations in KT candidates and recipients are more likely to be administered by their primary care providers, while vaccines that differ from the routine schedules, including the HPV, are more likely to be administered by transplant professionals, who are likely to be more familiar with dosing them appropriately (4,67). Thus, it is important for both general pediatricians and pediatric transplant nephrologists to be aware of the immunization guidelines for KT candidates and recipients and stay in close communication, to ensure an ongoing fully immunized status for their patients (4).…”
Section: Discussion: Strategies To Improve the Suboptimal Hpv Immuniz...mentioning
confidence: 99%
“…Worldwide, the estimated lifetime probability of being infected is greater than 80% for women and 90% for men ( 12 ). Certain types, including HPV 16, −18, −31, −33, −35, −39, −45, −51, −52, −56, −58 and −59, are responsible for greater than 95% of HPV-related cancers ( 4 , 13 ). HPV has been identified as a cause for cervical, vaginal, vulvar, penile, anal, and oropharyngeal cancers in >91%, 75%, 69%, 63%, 91% and 70%, respectively ( 4 , 14 ).…”
Section: Hpv: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations